2016
DOI: 10.1161/jaha.116.003477
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds, Vascular Risk Factors, and Magnetic Resonance Imaging Markers: The Northern Manhattan Study

Abstract: BackgroundCerebral microbleeds (CMBs) represent intracerebral hemorrhages due to amyloid angiopathy or exposure to modifiable risk factors. Few community‐based stroke‐free studies including blacks and Hispanics have been done.Methods and ResultsThe Northern Manhattan Study (NOMAS) is a stroke‐free, racially and ethnically diverse cohort study. Brain MRI was performed in 1290 participants, 925 of whom had available T2* gradient‐recall echo data. We used multivariable logistic regression to examine the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 31 publications
5
29
3
5
Order By: Relevance
“…18, 19 In the ARIC study, no significant difference in risk of CMB presence or location were detected by race. Two prior racially and ethnically diverse studies on CMBs revealed no difference in CMB frequency between black, white and Hispanic individuals 20, 21 . Despite the association of CMBs with imaging markers of small-vessel disease, diabetes was not associated with CMBs in the present study or in the Framingham or Rotterdam studies.…”
Section: Discussionmentioning
confidence: 75%
“…18, 19 In the ARIC study, no significant difference in risk of CMB presence or location were detected by race. Two prior racially and ethnically diverse studies on CMBs revealed no difference in CMB frequency between black, white and Hispanic individuals 20, 21 . Despite the association of CMBs with imaging markers of small-vessel disease, diabetes was not associated with CMBs in the present study or in the Framingham or Rotterdam studies.…”
Section: Discussionmentioning
confidence: 75%
“…ЦМК обнаружены у 44% пациентов, что соответствует данным литературы, со-гласно которым маркер обнаруживается у 35-71% пациен-тов с ИИ [8]. Указанная частота выявления ЦМК значи-тельно выше, чем в популяции, -5% по данным обследова-ния когорты The Northern Manhattan Study (NOMAS) [9].…”
Section: о р и г и н а л ь н ы е и с с л е д о в а н и я и м е т о д unclassified
“…Serebral mikrokanamalar (SMK) çapı 5 mm'den küçük, yuvarlak ve hemosiderin gibi kan yıkım ürünlerine duyarlı T2 gradient EKO sekanslarında hipointens görünen lezyonlardır (3,4,5). SMK normal yaşlanma ile artış gösterebilir, ancak aynı zamanda hipertansiyon gibi vasküler risk faktörleri, serebrovasküler hastalıklar, kognitif performans ve alzheimer hastalığıyla da ilişkili olabileceği bildirilmiştir (3,5).…”
unclassified
“…SMK normal yaşlanma ile artış gösterebilir, ancak aynı zamanda hipertansiyon gibi vasküler risk faktörleri, serebrovasküler hastalıklar, kognitif performans ve alzheimer hastalığıyla da ilişkili olabileceği bildirilmiştir (3,5).…”
unclassified
See 1 more Smart Citation